Re-examining success : raising pupils' examination performance at secondary school : systems, techniques, processes and partners - Hughes, David W (Teacher) (Practical teaching, 2020)
Provides the research and practical insights required for secondary schools to radically review and remodel exam preparation provision with a view to ensuring more pupils, particularly those that are vulnerable, can perform to their potential.